(untitled) (UNED Research Journal, 2023)
Introduction: Consumption of fresh tomatoes has increased over the years and production systems (conventional or hydroponic), harvest and post-harvest practices, irrigation water and harvest containers, can affect the microbiological quality of the final product. Objective: To compare the microbiological quality of the cultivated or harvested fruit, the irrigation water, and the harvest containers in two tomato production farms (conventional and hydroponic). Methods: We carried out three sampling visits in each farm (repetitions), taking, in each repetition, 3 tomatoes of each type (composite sample), 50 ml of irrigation water and swabbing 50cm2 of the surface of three harvest containers (composite sample). We determined indicator microorganisms such as total aerobic mesophilic count, mold and yeast count, total coliforms, thermotolerant coliforms and E. coli. Presence of Listeria monocytogenes was also analyzed in fruits. We applied student’s t-tests at a significance level of 5%. Results: Total aerobic mesophilic and mold and yeast counts of hydroponic tomato were significantly lower than in conventional tomato, while no difference in total coliform counts and E. coli was detected. L. monocytogenes was absent in all samples. The total aerobic mesophilic count was higher in the harvest containers of the conventional farm. In both farms, irrigation water was not considered a source of contamination since it had very low levels of total coliforms, thermotolerant coliforms, and E. coli. Finally, an adequate control during harvesting was presumed, having found no difference in the microbiological indicators between the cultivated and harvested tomato. Conclusion: Hydroponic tomatoes are more likely to have a better microbiological profile and longer shelf life compared to conventionally grown tomatoes, evidencing the importance of environmental control and cleaning and disinfection of all elements used in the farming, harvesting and postharvest processes.